Behavior and distribution of American marten (Martes americana) in relation to snow and forest cover on the Kenai Peninsula, Alaska - Baltensperger, Andrew Philip, author; Andelt, William F. (William Frank), advisor; Crooks, Kevin R., committee member; Hiemstra, Chris, committee member; Morton, John M., committee member (Colorado State University. Libraries, 2009)
Marten are sensitive to cold temperatures and normally rely on an insulating snow-pack and sufficient forest structure for thermal protection in winter. Low densities of marten on the western Kenai Peninsula, Alaska have commonly been attributed to shallow snow and habitat conditions that may not be conducive to supporting stable marten populations. This research examined the interactions between marten behavior in relation to available snow and habitat conditions at forest stand, home range, and landscape scales. Marten were radio-collared and back-tracked in three study areas in the Kenai Mountains and Kenai Lowlands to investigate habitat selection and the effects of snow conditions on the movement and resting behavior of marten. An aerial digital videography survey, supplemented by trapping, museum and Kenai National Wildlife Refuge (KENWR) records, was used to generate a minimum landscape distribution estimate of marten on the Kenai Peninsula. Videography detections were overlaid with Geographic Information Systems (GIS) layers for spruce-bark beetle damage and fire history on the Kenai Peninsula. We also tabulated the number of days marten were exposed to conditions in which the subnivean environment was not insulated from below freezing ambient temperatures. Trends in maximum snow depths were calculated by fitting regression lines to historic snow records at Kenai weather stations since 1931.Results demonstrated that marten chose rest sites in structures that would maximize thermodynamic efficiency given the availability of insulating snow cover and warm resting structures. While traveling, marten selected snow and habitat types largely in proportion to their availability at the home-range scale. Movement paths were more tortuous through habitat patches with higher than average canopy densities. Aerial videography surveys detected 32 locations of marten and indicated that the distribution of marten has expanded into the Kenai Lowlands where marten had previously not been reported in any abundance since the beginning of the 20th century. Detections occurred four times as frequently in a large post fire sere burned in 1947 in contrast to an area burned in 1969. Marten were detected in areas extensively damaged by spruce-bark beetles in just six instances and were twice as likely to be located outside of beetle-damaged areas. Average numbers of stress days were inversely related to elevation and the associated differences in snowfall associated with elevation. Analyses of regional maximum yearly snow depths indicated that maximum snow depths have been increasing by 0.29 cm/year in the Kenai Mountains, whereas trends have remained relatively constant in other regions of the Kenai Peninsula. Variations in available snow pack, forest maturity and the availability of resting structures may explain recent shifts in distribution at the landscape level.
Department Head: Kenneth Ray Wilson.